Spirometric evaluation of gastroesophageal reflux disease (gerd) associated cough and asthma - Ahmad, Amjad F.; AL-Ameen, Afraa M.; Jassim, Shaimaa A. H. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Gastroesophageal reflux disease can lead to esophageal complications, including esophagitis, ulceration, stricture, hemorrhage, and Barrett’s esophagus. However, the spectrum of problems associated with GERD has expanded to extra esophageal sites. Chronic cough and asthma are two clinical problems caused or triggered by GERD. Spirometric changes among GERD associated cough and asthma still a topic of ongoing research.Objectives: This study was designated to evaluate the spirometric picture of GERD associated cough and asthma subjects in relation to different clinical aspects of the disease including body mass index (BMI), disease duration, presence or absence of symptoms as well as endoscopic findings.Subjects and methods: Ninety adult subjects (90) of either sex with a mean age of 40.5±12 year are involved in this study. Fifty five (55) GERD associated cough and asthma subjects served as test group while the remaining (35) served as control group. Each subject underwent spirometry and gastric endoscopy in Pulmonary Function and Endoscopy Units respectively at Ibn-Sina Teaching Hospital /Mosul.Results: Spirometric data of the control group were within the normal predicted range (80-120%) thus excluding the possibility of any asymptomatic obstructive airway disease. Whereas, the measured spirometric parameters (forced vital capacity (FVC), forced expiratory volume in 1 second ratio (FEV1%), peak expiratory flow (PEF), and forced mid expiratory flow(FMF) are significantly reduced in the test group with a clear restrictive pattern among the overweight subjects. In addition, neither the presence nor duration of symptoms affected the spirometric picture of the GERD associated cough and asthma subjects, unlike those with positive endoscopy findings who revealed significant obstructive pattern when compared to those with negative endoscopy findings.Conclusions: GERD associated cough and asthma subjects with positive endoscopy findings showed obstructive pattern of spirometry irrelevant to the presence or absence of symptoms or duration of the disease.